2003
DOI: 10.1093/jac/dkg457
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial susceptibility of a vancomycin-resistant Staphylococcus aureus strain isolated at the Hershey Medical Center

Abstract: Staphylococcus aureus strain HMC3 isolated at the Hershey Medical Center, was resistant to vancomycin (VRSA) through the presence of the vanA resistance gene; it also contained mecA, erm(A), erm(B), tet(K) and aac(6')-aph(2"), conferring resistance to licensed beta-lactams, macrolides, tetracycline and aminoglycosides. HMC3 also had alterations in GyrA and GrlB and was resistant to available quinolones. Experimental drugs with low MICs (<2 mg/L) for VRSA HMC3 included cephalosporins BAL9141 and RWJ-54428; glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(137 citation statements)
references
References 11 publications
1
132
1
3
Order By: Relevance
“…Oritavancin is a lipoglycopeptide antibiotic and is structurally very similar to vancomycin. Despite the structural similarity, oritavancin retains in vitro activity against vancomycin-intermediate and vancomycin-resistant S. aureus strains (33). However, in one study, the MICs were higher for VISA than for MSSA or MRSA, and a time-kill analysis demonstrated reduced bactericidal activity against VISA strains (203).…”
Section: Potentially Active Antimicrobials In Developmentmentioning
confidence: 98%
“…Oritavancin is a lipoglycopeptide antibiotic and is structurally very similar to vancomycin. Despite the structural similarity, oritavancin retains in vitro activity against vancomycin-intermediate and vancomycin-resistant S. aureus strains (33). However, in one study, the MICs were higher for VISA than for MSSA or MRSA, and a time-kill analysis demonstrated reduced bactericidal activity against VISA strains (203).…”
Section: Potentially Active Antimicrobials In Developmentmentioning
confidence: 98%
“…In the developing countries nowadays multiple antibiotic resistance have been observed among important pathogens viz., Escherichia coli; MRSA, VREF; Klebsiella; Vibrio etc (Bozdogan et al, 2003;Byarugaba, 2004;Soulsby, 2005;Zhang et al, 2006). Uncontrolled and widespread application of antibiotics in both human and veterinary medicines is equally responsible for increase in prevalence of antibiotic-resistant bacterial infections, and emergence of new antimicrobial resistant pathogenic strains of various infectious agents.…”
mentioning
confidence: 99%
“…LZ acts by preventing the formation of 70S ribosome complex that is responsible for the initiation of protein synthesis, by binding to the 23S subunit of the 50S subunit [25]. However, enterococcal resistance to the drug occurs due to mutation of the ribosomal binding site [26].…”
Section: Resultsmentioning
confidence: 99%